Implementation of Building Recognition Android App - Sharma, Apoorv; Singh, Amit kumar (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Augmented Reality (AR) is a view of a real-world mixed with and/or superimposed by virtual objects. Therefore, one of the most important key techniques of implementing an AR is recognizing the environment so that it can correctly determine the virtual objects to be displayed on the multimedia representing the real-world. This paper reviews the “Method of Recognizing Objects in a Picture for Mobile AR Using Electronic Maps.” Then we describe the implementation of the method and an application on an Android mobile in detail.